Reciprocity and the Interaction between the Unemployed and the Caseworker - Gerard J. Van den Berg; Iris Kesternich; Gerrit Müller; Bettina Siflinger (Center for Economic Studies and ifo Institute (CESifo), 2019)
We investigate how negatively reciprocal traits of unemployed individuals interact with "sticks" policies imposing constraints on individual job search effort in the context of the German welfare system. For this we merge survey data of long-term unemployed individuals, containing indicators of reciprocity as a personality trait, to a unique set of register data on all unemployed coached by the same team of caseworkers and their treatments. We find that the combination of a higher negative reciprocity and a stricter regime have a negative interaction effect on search effort exerted by the unemployed. The results are stronger for males than for females. Stricter regimes may therefore drive long-term unemployed males with certain types of social preferences further away from the labor market.
Keywords: D90; J16; J24; J64; N44; 330; behavioral response; active labor market policy; monitoring; welfare; job search